Abortive Infection of Sporulating Bacillus subtilis 168 by φ2 Bacteriophage - Ito, Junetsu (1971)
Bacteriophage φ2 is unable to replicate in Bacillus subtilis 168. Although some phage deoxyribonucleic acid (DNA) synthesis can occur, the DNA made is not biologically active and sedimentation analysis reveals that it is smaller in size than that of mature DNA or DNA isolated from φ2-infected permissive hosts. Messenger ribonucleic acid hybridizable with φ2 DNA is also synthesized in φ2-infected cells of 168. Mutants of 168 which are permissive hosts for φ2 have been isolated. These mutants are defective in sporulation and possess the phenotype of “early sporulation mutants.” The majority map in two locations, one near the lys locus opposite the trp locus (spoA locus) and the other tightly linked to a phe locus.